Diversity of Cryptosporidium in brush-tailed rock-wallabies (Petrogale penicillata) managed within a species recovery programme. Issue 2 (August 2015) - Vermeulen, Elke T.; Ashworth, Deborah L.; Eldridge, Mark D.B.; Power, Michelle L.
Highlights Cryptosporidium diversity was investigated in a BTRW as part of a recovery programme. Faecal samples from captive bred, supplemented and wild wallabies were screened. Cryptosporidium isolates were identified at three gene loci using PCR. Diverse species of Cryptosporidium were identified across populations. Both specific, C. fayeri, and broad host species, C. meleagridis, were identified.